Pengaruh Tekanan Keluarga, Pengawasan, dan Integritas Prajuru Terhadap Kecenderungan Kecurangan Akuntansi Pada LPD di Kecamatan Seririt - Komang Diah Ayu Suarmini; Edy Sujana (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
Purpose of this study was to determine the effect of family pressure, supervision, and integrity of the prajuru and their influence on accounting fraud in the LPD in Seririt sub-district. Quantitative research is a type of this research. Primary data was obtained through questionnaire distributed to respondents and measured using a Likert scale. The population in this study were 75 LPD employees in Seririt sub-district and the number of samples was 48 LPD employees taken by purposive sampling. Data analysis used linier regression. In analyzing data using SPSS 20.0 for windows. The results of this study are: (1) family pressure has a positive and significant effect on the tendency of accounting fraud in the LPD in Seririt District, (2) supervision has a negative and significant effect on the tendency of accounting fraud in the LPD in Seririt District, (3) the integrity of prajuru partially has a negative and significant effect on the tendency of accounting fraud in the LPD in Seririt district.